2014
DOI: 10.1097/brs.0000000000000382
|View full text |Cite
|
Sign up to set email alerts
|

T1 Pelvic Angle (TPA) Effectively Evaluates Sagittal Deformity and Assesses Radiographical Surgical Outcomes Longitudinally

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
91
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(93 citation statements)
references
References 18 publications
2
91
0
Order By: Relevance
“…This T1PA value accounts for both SVA and pelvic tilt, and according to the several references, this might be reduced to less than 10° in order to achieve optimal surgical outcome both radiologically and clinically811). The representability of T1PA instead of SVA was also reflected in our series; 11° for the normal SVA group and 22° for positive SVA group even after correction.…”
Section: Discussionsupporting
confidence: 63%
“…This T1PA value accounts for both SVA and pelvic tilt, and according to the several references, this might be reduced to less than 10° in order to achieve optimal surgical outcome both radiologically and clinically811). The representability of T1PA instead of SVA was also reflected in our series; 11° for the normal SVA group and 22° for positive SVA group even after correction.…”
Section: Discussionsupporting
confidence: 63%
“…Another parameter recently described in the literature, and assessing the spinopelvic alignment is the T1 pelvic angle (TPA) [15][16][17]. The latter is defined as the angle between the line from the femoral head axis to the centroid of T1 and the line from the femoral head axis to the middle of the S1 endplate.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review concluded that there was only level IV evidence in support of the effectiveness of physical therapy, chiropractic care, and bracing in the treatment of adult scoliosis patients and level III evidence for steroid injection [66]. The long-term successful rate of conservative treatment of symptomatic adult scoliosis was only 27% [68,69].…”
Section: Treatmentmentioning
confidence: 99%
“…The poor outcomes of the above interventions are not unexpected, as the treatments were directed towards pain relief, but not the deformities and the global imbalance that are causing the symptoms [69]. Treatment approaches that target spinal deformities yielded better results in terms of reduction in pain and disability ratings in ADIS patients [70][71][72][73][74][75][76].…”
Section: Treatmentmentioning
confidence: 99%